Elasto-viscoplastic behaviour of a polyvinylidene fluoride (PVDF) in tension. (September 2015) - Reis, J.M.L.; Motta, E.P.; da Costa Mattos, H.S.
Abstract: The present paper is concerned with the plasticity of a polyvinylidene fluoride (PVDF) in tension. Strain rate strongly influences the plastic behaviour, but the variation of the elastic properties is almost negligible within the range of strain rates considered in the study (from 1.6 × 10 −4 s −1 up to 1.6 × 10 −1 s −1 ). In particular, the yield stress and the ultimate tensile strength are strongly rate-dependent. A one-dimensional elasto-viscoplastic phenomenological model is proposed and analysed. Despite the nonlinearity of the model equations, only one tensile test performed with variable strain rate is sufficient to identify all material parameters. Model predictions are compared with experiments showing good agreement.